1990
DOI: 10.1128/jb.172.12.6704-6712.1990
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Erwinia uredovora carotenoid biosynthetic pathway by functional analysis of gene products expressed in Escherichia coli

Abstract: functions as a precursor of vitamin A in mammals (G. A. J. Pitt, in I. Osler, H. Gutmonn, and U. Solms, ed., Carotenoids-1971Carotenoids- , 1971). The enzymes and genes which mediate the biosynthesis of cyclic carotenoids such as 13-carotene are virtually unknown. We have elucidated for the first time the pathway for biosynthesis of these carotenoids at the level of enzyme-catalyzed reactions, using bacterial carotenoid biosynthesis genes. These genes were cloned from a phytopathogenic bacterium, Erwinia urede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
383
1
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 548 publications
(401 citation statements)
references
References 27 publications
9
383
1
2
Order By: Relevance
“…First, CRT-I type of phytoene desaturases have been cloned from the bacteria Rhodobacter capsulatus [13], Erwinia uredovora and E. herbicola (crtl genes) [14,15] and from the fungus Neurospora crassa (aLl gene) [16] and sequenced. Then, the genes encoding phytoene desaturases from cyanobacteria [12,17], green algae and plants [11,18,19] have been isolated (pds genes).…”
Section: Discussionmentioning
confidence: 99%
“…First, CRT-I type of phytoene desaturases have been cloned from the bacteria Rhodobacter capsulatus [13], Erwinia uredovora and E. herbicola (crtl genes) [14,15] and from the fungus Neurospora crassa (aLl gene) [16] and sequenced. Then, the genes encoding phytoene desaturases from cyanobacteria [12,17], green algae and plants [11,18,19] have been isolated (pds genes).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, Escherichia coli BL21 (DE3) cells (Novagen) were transformed with combinations of pACCAR25DcrtB and the expression constructs pETb-MPSY3, pETa-SPSY1, pETa-SPSY3, or empty vector pET23b (1). Carotenoids were extracted (Gallagher et al, 2004), resuspended in methanol, and subjected to HPLC analysis (Quinlan et al, 2007); zeaxanthin diglucoside was identified as before (Gallagher et al, 2004) and in comparison with literature data (Misawa et al, 1990).…”
Section: Functional Complementationmentioning
confidence: 99%
“…Maize PSY3 and sorghum PSY1 and PSY3 cDNAs were subcloned into the pET23 expression vector (Novagen) and transformed into Escherichia coli harboring pACCAR25DcrtB, which carries a bacterial carotenoid gene cluster missing the bacterial PSY gene crtB (Misawa et al, 1990). Cells produce the pathway end product, zeaxanthin diglucoside, only when a functional PSY enzyme is present; a peak corresponding to this end product is seen in an HPLC chromatogram of extracted carotenoids from positive control cells containing the entire carotenoid cluster, including bacterial PSY (pACCAR25; Fig.…”
Section: Psy3 Encodes a Functional Psymentioning
confidence: 99%
“…For example, for lycopene production, crtB, crtE, and crtI from Erwinia uredovora (now Pantoea ananatis) were cloned into E. coli ( Figure 4). [31] Varying the order of genes in the crt operon affected the titer of lycopene which is presumable due to the change in the expression level of each gene. [32] Choosing the gene sources was also important.…”
Section: Introduction Of Heterologous Genesmentioning
confidence: 99%